Association between adherence to the Mediterranean diet with cardiometabolic risk factors: a cross-sectional study on PERSIAN cohort study in Fasa - Milad Bagheri; Mehran Nouri; Reza Homayounfar; Masoumeh Akhlaghi (Scientific Reports, 2023)
Abstract The relationship between Mediterranean diet and obesity-related markers is a matter of debate. We investigated the association between adherence to the Mediterranean diet and anthropometric indices, body composition, and cardiometabolic risk factors in Iranian population. The cross-sectional study was performed on data of 3386 participants from Fasa PERSIAN cohort study. The Mediterranean diet score (MDS) was calculated based on consumption of 11 food groups (unrefined cereals, potatoes, fruits, vegetables, legumes, fish, red meat, poultry, dairy, olive oil, and alcoholic beverages). The association between MDS and cardiometabolic risk factors was examined by linear regression analysis. MDS was inversely associated with waist circumference (β =  − 1.11; P = 0.033), waist-to-hip ratio (β =  − 0.007; P = 0.011), waist-to-height ratio (β =  − 0.009; P = 0.015), fasting glucose (β =  − 3.59; P = 0.001), and HDL-cholesterol (β =  − 0.96; P = 0.031) in unadjusted model. After adjusting for energy intake, the associations of MDS with markers of abdominal obesity and HDL-cholesterol disappeared. In fully adjusted model, MDS showed inverse relationships with waist-to-hip ratio (β =  − 0.005; P = 0.037) and fasting glucose (β =  − 2.71; P = 0.013). In conclusion, MDS showed an inverse relationship with fasting glucose and waist-to-hip ratio. Since energy intake increased along with increasing MDS, adherence to the Mediterranean diet may associate with lower abdominal obesity and better glycemic control if an energy-controlled Mediterranean diet is used.